Pengaruh Brand Experience dan Trust Terhadap Customer Satisfaction dengan Mediasi Brand Love - Cahyo, Septian Dwi; Maziyah, Siti; Patmasari, Eka Kurnia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to examine the influence of brand experience and brand trust on customer satisfaction with brand love as a mediating variable. The case study focuses on users of MS Glow at Store Sinok Ayu, Kendal. A quantitative method was employed with data collected through online questionnaires from 118 respondents. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) via WarpPLS 8.0. Seven hypotheses were tested to assess both direct and mediated effects. The results reveal that brand experience, brand trust, and brand love have a positive and significant effect on customer satisfaction. Furthermore, brand love is found to significantly mediate the relationship between brand experience and customer satisfaction, as well as between brand trust and customer satisfaction. This study is limited to a single local skincare brand (MS Glow) and one geographic location, which may limit the generalizability of the findings. The findings suggest that companies should enhance brand experience and trust to foster emotional connections, thereby increasing customer satisfaction. This research enriches the literature by positioning brand love as a mediating variable, offering insights into the emotional and cognitive mechanisms driving customer satisfaction in the skincare industry.